2016
DOI: 10.1038/ncomms12722
|View full text |Cite
|
Sign up to set email alerts
|

Observational learning computations in neurons of the human anterior cingulate cortex

Abstract: When learning from direct experience, neurons in the primate brain have been shown to encode a teaching signal used by algorithms in artificial intelligence: the reward prediction error (PE)—the difference between how rewarding an event is, and how rewarding it was expected to be. However, in humans and other species learning often takes place by observing other individuals. Here, we show that, when humans observe other players in a card game, neurons in their rostral anterior cingulate cortex (rACC) encode bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 39 publications
4
79
0
Order By: Relevance
“…First, previous neuroimaging studies have shown evidence of social prediction errors consistently in the same ACCg region using smaller samples ( n = 12, 14 and 15) of TD individuals (Apps et al , 2012, 2013 a , 2015). In addition, in a recent single-unit recording study in humans (Hill et al , 2016), social prediction errors were identified in the ACCg when only 10 patients were present. Although the method is different, this suggests that social prediction errors may be a reliable property of the response in this region, and only a small number of TD individuals are required to elicit this response.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…First, previous neuroimaging studies have shown evidence of social prediction errors consistently in the same ACCg region using smaller samples ( n = 12, 14 and 15) of TD individuals (Apps et al , 2012, 2013 a , 2015). In addition, in a recent single-unit recording study in humans (Hill et al , 2016), social prediction errors were identified in the ACCg when only 10 patients were present. Although the method is different, this suggests that social prediction errors may be a reliable property of the response in this region, and only a small number of TD individuals are required to elicit this response.…”
Section: Discussionmentioning
confidence: 91%
“…Third, single-unit recordings in non-human primates show that a larger proportion of ACCg neurons, compared with those in orbitofrontal cortex or ACCs, track the rewards and outcomes of others (Chang et al , 2013). Hill et al (2016) recently replicated this in humans by demonstrating that neurons in the rostral ACC (putatively ACCg) encode both the expected outcome and discrepancies between the expected and actual outcome of another person’s decision (i.e. social prediction errors) when learning from another through observation.…”
Section: Introductionmentioning
confidence: 83%
“…The portion of the VMPFC identified in this study has been consistently linked to the processing of the value of rewards for ourselves and also others (Rushworth & Behrens, 2008; Smith, Clithero, Boltuck, & Huettel, 2014). Both neurophysiological recordings in monkeys and neuroimaging studies in humans show that neurons in this region predict the value of rewards that we – and others – will receive (Apps et al., 2016; Garvert, Moutoussis, Kurth‐Nelson, Behrens, & Dolan, 2015; Hill, Boorman, & Fried, 2016; Nicolle et al., 2012). It is therefore possible that activity in this study could be related to the differential payoffs to self and other, rather than to fairness per se.…”
Section: Discussionmentioning
confidence: 99%
“…W. Chang, Gariepy, & Platt, 2013;Rudebeck et al, 2006). Adjacent areas of cingulate cortex and other medial frontal regions have also been implicated in tracking the behaviour and intentions of other agents (Fatfouta, Meshi, Merkl, & Heekeren, 2018;Haroush & Williams, 2015;Hill, Boorman, & Fried, 2016;Wittmann et al, 2016;Kyoko Yoshida et al, 2011;K. Yoshida et al, 2012).…”
Section: Composition Of a Social Networkmentioning
confidence: 99%